Development of dry film lubricants for highly loaded contacts - Barman, Kanika (2016)
This thesis motivated by concerns over fretting damage in the aerospace engine disc dovetail joint in Ti6Al4V. The dovetail joint behaviour was investigated using a cylinder-on-flat contact geometry setup and fretting amplitude of 300 µm, a frequency of 2.5 Hz and load of 575 N was used. The thesis is concerned about an experimental investigation of the fretting behaviour of Ti6Al4V coated with a commercially available MoS2-based dry film Lubricant (DFL). Sample performance was determined via analysis of fretting loops, condition of coefficient of friction, Scanning Electron Microscopy (SEM) images of wear scars on plan view and cross section, Energy-dispersive X-ray spectroscopy (EDS) and X-ray Photoelectron Spectroscopy (XPS) analysis. To study the influence of contact geometry on fretting wear, tests were conducted using cylinders with radii of 15 mm, 80 mm and 160 mm with DFL thicknesses between 12 µm and 86 µm. All tests showed a high level of repeatability. Three stages phenomenological model of the polymer bonded dry film lubricant in the lifetime of the system were identified. In the first stage, the DFL wore with a volumetric rate that was proportional to the number of cycles (under a given load), until the thickness of the DFL was reached. In the second stage, a thin low friction surface layer existed, with its durability being proportional to the contact pressure. In the third stage, metal-metal contact resulted in short-term instabilities in the coefficient of friction and the DFL system was regarded to have failed. A phenomenological model that predicts coating lifetime is developed, which can be applied regardless of contact geometry, thickness and loads. The model was extended to a system in presence of a Cu-Ni-In underlayer, as DFL behaviour was determined and analysed using the same three stage approach. Higher roughness results in reduced rates of change in behaviour and a significant extension of the stage II duration over which the surface material is made up of a mixture of DFL and metal, accordingly, the high durability of the system with the Cu-Ni-In underlayer is primarily ascribed to the high roughness of the underlayer in its as-sprayed form onto which the DFL was deposited. The effect of PTFE and graphite additives was determined. 4.77 wt. %, 9.08 wt. % PTFE and 4.76 wt. % graphite extended DFL lifetime. The PTFE appears to slow stage I, the wear of the DFL layer, but once the metallic surface is reached the mechanism of wear of DFL system appears unchanged. Lifetime of the graphite extended significantly with stage I and stage II maintaining lower coefficient of friction, that it was not possible to run tests to completion, even when the wear scar penetrates significantly through the metal. An alternative mechanism appears to be active, thus requires further investigation.